Resource provision in the construction management system considering uncertainty and risk factors - Voitovych, V. (Ways to Improve Construction Efficiency, 2024)
This article explores a comprehensive approach to resource provision within the construction management system, taking into account the factors of uncertainty and risk inherent in modern investment and construction projects. The complexity of today’s construction environment-driven by dynamic market fluctuations, significant variability in the cost of material and technical resources, disruptions in global and local supply chains, as well as internal organizational, technical, and technological risks–necessitates a rethinking of traditional resource management practices in construction. The study substantiates the need to develop an adaptive resource provision system that is resilient to external impacts and capable of responding promptly to changes in the project implementation environment. Contemporary scientific approaches to construction production organization, logistics, risk management, and strategic management are analyzed, enabling the integration of these elements into a unified conceptual model. Particular attention is paid to the use of digital technologies, especially Building Information Modeling (BIM), as a key tool for integrating logistics, resource planning, scheduling, and management processes into a single digital decision-support system. A resource provision model is proposed, based on a combination of scenario modeling methods, automated decision-making, and flexible resource flow management. This approach enables the effective implementation of construction projects even under conditions of high turbulence, minimizing the risks of schedule disruptions and resource overruns.